Contemporary rehearsal practice : Anthony Neilson and the devised text - Cassidy, Gary, 1969- (Routledge, 2021)
"This book provides the first comprehensive study of Anthony Neilson's unconventional rehearsal methodology. Neilson's notably collaborative rehearsal process affords an unusual amount of creative input to the actors he works with and has garnered much interest from scholars and practitioners alike. This study analyses material edited from 100 hours of footage of the rehearsals of Neilson's 2013 play Narrative at the Royal Court Theatre, as well as interviews with Neilson himself, the Narrative cast, and actors from other Neilson productions. Replete with case studies, Gary Cassidy also considers the work of other relevant practitioners where appropriate, such as Katie Mitchell, Forced Entertainment, Joan Littlewood, Peter Brook, Complicite's Simon McBurney, Stanislavski and Sarah Kane. Contemporary Rehearsal Practice will be of great interest to scholars, students and practitioners of theatre and performance or has an interest in rehearsal studies"--